2013
DOI: 10.1007/s00213-013-3069-x
|View full text |Cite
|
Sign up to set email alerts
|

Cue-induced resumption of heroin and cocaine seeking in rats using a conflict model of abstinence and relapse

Abstract: The implementation of negative consequences for drug seeking can result in its cessation just as they might in human addicts. Similarly, exposure to drug cues can lead to resumption of drug seeking. This model may be useful for studying the mechanisms underlying abstinence and relapse and for developing strategies to prevent relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Our finding of incubation of methamphetamine craving after punishment extend previous reports in which investigators used response-contingent shock-or shock-barrierbased conflict procedures to study drug relapse induced by exposure to drug priming (Panlilio et al, 2005), drugassociated cues (Cooper et al, 2007;Economidou et al, 2009;Peck et al, 2013), or drug-associated contexts (Marchant et al, 2013a). An unexpected finding was that incubation of food craving after punishment was procedure-dependent and was only observed in the between-subject assessment.…”
Section: Incubation Of Methamphetamine and Food Craving After Punishmentsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding of incubation of methamphetamine craving after punishment extend previous reports in which investigators used response-contingent shock-or shock-barrierbased conflict procedures to study drug relapse induced by exposure to drug priming (Panlilio et al, 2005), drugassociated cues (Cooper et al, 2007;Economidou et al, 2009;Peck et al, 2013), or drug-associated contexts (Marchant et al, 2013a). An unexpected finding was that incubation of food craving after punishment was procedure-dependent and was only observed in the between-subject assessment.…”
Section: Incubation Of Methamphetamine and Food Craving After Punishmentsupporting
confidence: 86%
“…Over the years, several studies have shown that punishment significantly decreases and even eliminates opiate and psychostimulant self-administration (Johanson, 1975;Panlilio et al, 2003;Pelloux et al, 2007;Smith and Davis, 1974). More recently, we and others have begun to use punishment-based procedures to study relapse to drug seeking induced by drug-priming injections (Panlilio et al, 2003;Panlilio et al, 2005) or drug cues and contexts (Cooper et al, 2007;Economidou et al, 2009;Marchant et al, 2013a;Peck et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the electric barrier phase drug was available under a FR2 20-s timeout reinforcement schedule for 30 min/day. This schedule of reinforcement has been used to establish abstinence (no presses on the active lever) without numerous daily sessions that could lead to catheter failure (Cooper et al, 2007;Barnea-Ygael et al, 2012;Peck et al, 2013). Further, the electric barrier current did not exceed 1.00 mA for any individual rat.…”
Section: Electric Barriermentioning
confidence: 99%
“…Recently, we (Peck et al, 2013) used a similar abstinence conflict model with heroin self-administration. We found that abstinence was achieved for all heroin-seeking rats by increasing the electric shock intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies demonstrated relapse to heroin seeking after electric barrier suppression of heroin seeking. Peck et al [136] reported that a higher proportion of heroin-trained rats than cocaine-trained rats resume drug seeking after electric barrier suppression of drug self-administration during a relapse test in which the electric barrier was maintained. For both drugs, the authors observed large individual differences during the relapse tests, most likely because the tests were performed in the presence of the electric barrier.…”
Section: Forced Abstinence and Incubation Of Drug Cravingmentioning
confidence: 99%